ID: 48. Issue 1 (November 2015) - Poh, Ashleigh Ren-yi; Lessene, Guillaume; Khakham, Yelena; Masson, Frederic; Preaudet, Adele; Putoczki, Tracy; O'Donoghue, Robert; Ernst, Matthias
<x xml:space="preserve">Abstract</x> Colorectal cancer is the second most commonly diagnosed cancer worldwide, and may develop sporadically or due to chronic colitis. Macrophages are a major component of the colorectal tumour microenvironment and may be broadly classified as classically-activated (CAM) 'inflammatory' or alternatively-activated (AAM) 'pro-angiogenic' macrophages. Hematopoietic Cell Kinase (Hck) is a myeloid-specific Src family kinase involved in alternative macrophage polarisation, which correlates with a poor prognosis in human colorectal cancer. To investigate the role of Hck in colorectal tumourigenesis, Hck mutant mice that express a constitutively active form of Hck (HckCA) were subjected to models of sporadic and colitis-associated colorectal cancer. In both models, HckCA mice demonstrated increased tumour size and multiplicity compared to wild-type animals. FACS analysis of tumour immune-cell infiltrates did not reveal a difference in the number of tumour-associated macrophages (TAMs) between genotypes; however, CD206+ alternatively-activated TAMs were significantly greater in HckCA mice compared to wild-type. Furthermore, qPCR analysis highlighted a significant increase in genes associated with alternative-macrophage activation in HckCA TAMs. To confirm the role of macrophages in HckCA-driven tumourigenesis, wild-type mice were reconstituted with HckCA bone-marrow, and subjected to sporadic or colitis-associated colon cancer induction, after which we observed an increased tumour burden and an AAM phenotype compared to wild-type bone-marrow recipients. Finally, we have shown that the inhibition of Hck using a small molecule inhibitor reduces alternative macrophage polarisation. Collectively, our results suggest that excessive Hck activation enhances colorectal tumourigenesis by facilitating alternative macrophage polarisation, which may be alleviated through the therapeutic targeting of this kinase.